Lighting Retrofit Scheme Economic Evaluation - Mohd Ab Halim, Mohd Firdaus; Azlan, Umar Al-Amani; Harun, Mohamad Haniff; Mohd Annuar, Khalil Azha; Manap, Mustafa; Johari, Siti Halma; Abdullah, Abdul Rahim; Hushim, Mohd Faisal (Institute Of Advanced Engineering And Science (IAES), 2017)
-